A scalable parallel factorization of finite element matrices with distributed Schur complements. Issue 5 (30th June 2016) - Maurer, Daniel; Wieners, Christian
Summary: We consider the parallel factorization of sparse finite element matrices on distributed memory machines. Our method is based on a nested dissection approach combined with a cyclic re‐distribution of the interface Schur complements. We present a detailed definition of the parallel method, and the well‐posedness and the complexity of the algorithm are analyzed. A lean and transparent functional interface to existing finite element software is defined, and the performance is demonstrated for several representative examples. Copyright © 2016 John Wiley & Sons, Ltd.